KEARIFAN LOKAL LILIFUK DI NUSA TENGGARA TIMUR DALAM PENGELOLAAN SUMBER DAYA LAUT BERKELANJUTAN - Hasriyanti Hasriyanti; Alief Saputro; Anugrah Isromi (Jurnal Environmental Science, 2021)
Local wisdom is an important sector that continues to be preserved by the Indonesian people, one of which is the local wisdom of lilifuk in East Nusa Tenggara. Lilifuk is one of the local wisdoms in the East Nusa Tenggara Province of Indonesia which has become a community culture in terms of managing marine resources. This study aims to determine the sustainable management of marine resources that exist in the local wisdom of lilifuk in East Nusa Tenggara. The type of research used is qualitative through literature studies. The scope of this research area is in East Nusa Tenggara, precisely in Kuanheun Village, West Kupang District, West Kupang Regency. In this study, the data collection method used is documentation, which is tracking written sources containing various themes and topics discussed. The data have been collected and analyzed using descriptive methods that describe what is being investigated. The results of this study indicate that in the management of lilifuk, the people of East Nusa Tenggara mobilize all elements to maintain and preserve lilifuk local wisdom, this is evidenced by the existence of five elements of society that play an important role, namely religious leaders, traditional leaders, village government, communities, and people who come from. from outside the village each of these elements has a responsibility and function according to the given role.